2019
DOI: 10.3390/cells8121596
|View full text |Cite
|
Sign up to set email alerts
|

GRK2 Mediated Abnormal Transduction of PGE2-EP4-cAMP-CREB Signaling Induces the Imbalance of Macrophages Polarization in Collagen-Induced Arthritis Mice

Abstract: Rheumatoid arthritis (RA) is characterized by the massive infiltration of various chronic inflammatory cells in synovia. In synovial fluid of patients with RA, M1 macrophages are dominant among all subtypes of macrophages, the mechanisms of macrophages polarization imbalance in RA has not been fully illuminated. The prostaglandin E2 (PGE2) augments M2 polarization in part via the cyclic adenosine monophosphate (cAMP)-cyclic AMP responsive element binding (CREB) signaling. However, previous study found constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…CREB is an important cAMP-responsive transcription factor. It has been found to be a constant stimulus of PGE2-induced abnormal cAMP-CREB signaling as well as the imbalance of inflammation [ 52 ]. we will further investigate whether CREB is involved in the regulation of PACER in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…CREB is an important cAMP-responsive transcription factor. It has been found to be a constant stimulus of PGE2-induced abnormal cAMP-CREB signaling as well as the imbalance of inflammation [ 52 ]. we will further investigate whether CREB is involved in the regulation of PACER in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…30 As expected, the results of our present study showed that the expression of EP2 receptor was obviously increased in DEN-induced HCC mice model, which suggested that EP2 expression was positively associated with the severity of disease. GRK2 with different subcellular localization acts different roles of intracellular signaling, 31 and membranous fraction of EP2 leading to activation of its downstream signals and inducing laryngeal carcinomas progression. 32 We detected the distribution changes of GRK2 and EP2 in HCC cells, and the membrane proteins were isolated from three HCC cell lines with stepwise metastatic potential through ultracentrifugation.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 can enhance the production of pro-inflammatory cytokines and chemokines, such as IL-6 and IL-17, by binding with exogenous ligands, like peptidoglycan, in FLS and peripheral blood mononuclear (PBMC) from RA patients, and trigger cartilage inflammation and degeneration (135). GRK2 prevents the shift of M1 into M2 macrophages by mediating PGE2-EP4-cAMP-CREB signaling in synovial macrophages (136). BTK activation induces B cells survival, proliferation, and differentiation by the SYK-BTK axis (137), which is an attractive therapeutic target for RA.…”
Section: Other Protein Targetsmentioning
confidence: 99%